Assessment of Essential and Toxic Element Intake from Sheep Dairy Products with Different Consumption Scenarios in an Organic Sheep Farm - Martina Pšenková; Róbert Toman; Ivona Jančo (Universitas Sebelas Maret, 2026)
Monitoring essential and toxic elements in milk and dairy products is important for protecting consumer health. Regular monitoring of these elements helps ensure the quality, safety, and nutritional value of dairy products. This study aimed to determine the concentrations of 8 elements (Ca, Mg, K, Zn, Se, Ni, Sr, and As) in sheep milk, sheep cheese, and traditional Slovak sheep products, including žinčica and bryndza. A total of 48 samples were collected from an ecologically managed sheep farm located in an undisturbed area of Slovakia. The highest concentrations were recorded for essential elements, particularly in solid sheep milk products such as sheep cheese and bryndza. Significant differences (p < 0.05) in element concentrations were observed among the analyzed products. Dietary intake assessment was based on 2023 Slovak dairy consumption data and on recommended consumption levels for selected dairy products. Risk assessment of toxic element intake revealed elevated exposure levels in relation to toxicological limits. Ni intake reached 50.77% of the tolerable daily intake (TDI) in bryndza and 40.00% in fresh sheep cheese. For As, the preliminary tolerable weekly intake (PTWI) reached 48.00% for žinčica and 30.60% for bryndza. These findings suggest that long-term excessive consumption of certain sheep products may negatively affect human health. Although sheep milk products are consumed less frequently than cow milk products, their high nutritional value and the detected levels of toxic elements highlight the need for continuous monitoring of element transfer into the food chain and its potential effects on human health.